Ocena postopkov delovnoterapevtske obravnave v programu rehabilitacije otrok s posebnimi potrebami - Albreht, Eva (Rehabilitacija (Ljubljana), 2019)
Background: A family-centred approach is crucial for successful rehabilitation programs of children with functional disorders. Aiming to provide high quality intervention for these children, it is very important to acknowledge opinions of parents and perspectives of occupational therapists. We wanted to evaluate these processes of care in developmental outpatient clinics of health centres in Slovenia by obtaining information from parents and occupational therapists. Methods: Participants were parents of children with functional disorders and occupational therapists from health centres. Children were up to 6 years old and had been included in the occupational therapy program for at least one year. The two questionnaires (Slovene translations of Measure of processes of care, MPOC; for occupational therapists, MPOCSP, and for parents, MPOC-20) were send to all health centres in Slovenia with developmental outpatient clinics. The parents participating in the study were randomly selected. Data were analysed using descriptive statistics. Results: There were 14 occupational therapists and 14 parents participating in the study. Parents reported good overall satisfaction with processes of care, but they were least satisfied with the provision of general and specific information about their children. The subscale "Providing general information" was ranked the lowest by the occupational therapists as well. The subscale "Respectful and supportive care" was ranked the highest. The parents and occupational therapists ranked individual subscales in the same order in terms of the average score. Conclusion: Based on the fact that parents and occupational therapists were least satisfied with the provision of general and specific information, we advise improvements in the exchange of information between parents and therapists. The results of our study are in agreement with previous results in Slovenia and abroad.
Keywords: assessment of processes of care; Child; delovna terapija; family-centered approach; Occupational therapy; ocena postopkov oskrbe; otrok; parents; starši; v družino usmerjen pristop